Development of an HPLC-UV Method for Quantification of Stattic - Sedaghat, Soheil; Molavi, Ommoleila; Faridi, Akram; Shayanfar, Ali; Rashidi, Mohammad R. (Current Pharmaceutical Analysis, 2019)
Background: Signal transducer and activator of transcription 3 (STAT3), an oncogenic protein found constitutively active in many types of human malignancies, is considered to be a promising target for cancer therapy. Objective: In this study for the first time, a simple and accurate method has been developed for the determination of a STAT3 dimerization inhibitor called stattic in aqueous and plasma samples. Methods: A reverse-phase high-performance liquid chromatography (RP-HPLC) composed of C18 column as stationary phase, and the mixture of acetonitrile (60%) and water (40%) as mobile phase with a UV detection at 215 nm were applied for quantification of stattic. The developed method was validated by Food and Drug Administration (FDA) guideline. Results: The method provided a linear range between 1-40 and 2.5-40 μg mL-1 for aqueous and plasma samples, respectively, with a correlation coefficient of 0.999. The accuracy (as recovery) of the developed method was found to be between 95-105% for aqueous medium and 85-115% for plasma samples. The precision (as relative standard deviation) for aqueous and plasma samples was less than 6% and 15%, respectively. The sensitivity of the developed method based on FDA guideline was 1 μg mL-1 for aqueous and 2.5 μg mL-1 for plasma samples. Conclusion: These results show that the established method is a fast and accurate quantification for stattic in aqueous and plasma samples.
Keywords: cancer